Apuração de custos nas universidades públicas federais: o caso da Universidade Federal de Sergipe - Menezes, Abel Smith (2024)
Objective: To propose a cost system model for the Federal University of Sergipe, in accordance with NBC TSP No. 34/2021. Methodology: The research method used was a single and exploratory case study, characterized as a descriptive research with a qualitative approach. Primary and secondary data were used and processed using the R System. Main Results: The proposed model using the UFS Cost Dashboard allows the observation of costs at various levels, for example: by expense element, by cost unit, by month, by macroprocess, among others. In addition, it allows the inclusion of other criteria for measuring costs, such as teaching hours and equivalent student. Furthermore, with the use of the UFS Cost Dashboard, the governance practices implemented at the Institution will occur even more efficiently and effectively with regard to the principles of transparency, integrity, and accountability. Theoretical and methodological contributions: This research provides a cost assessment model that can be easily adapted for federal public universities, based on data extraction from several different systems that are then integrated and related, using scripts for data processing and cost allocation according to the definition of the allocation criteria, through the free software R (R-Project 4.3.1) and assembly of a monitoring panel. Furthermore, this work will contribute to the literature regarding cost management in the public sector, specifically in the implementation of a cost system in federal public universities, which will allow the improvement of university management. Relevance and Originality: The indispensability of studies in the area of costs in the public service, mainly in Federal Higher Education Institutions (IFES), in view of the scenario of contingency of public resources by the Brazilian government, requires decisionmaking by public managers, based on information that allows greater efficiency in the application of public resources. Social and management contributions: In view of the results achieved, this research will enable assistance in the management of UFS resources, since a cost system model appropriate for the institution will promote a reduction in public spending, providing a better allocation of resources within UFS, with greater efficiency, transparency, and sustainability. With this, the public manager will comply with the principle of economy, not only applying what is recommended by law, but also managing the public good.